2004
DOI: 10.1186/1471-2407-4-40
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of MMP-11 (stromelysin-3) expression in mouse fibroblasts by cytokines, collagen and co-culture with human breast cancer cell lines

Abstract: Background: Matrix metalloproteinases (MMPs) are central to degradation of the extracellular matrix and basement membrane during both normal and carcinogenic tissue remodeling. MT1-MMP (MMP-14) and stromelysin-3 (MMP-11) are two members of the MMP family of proteolytic enzymes that have been specifically implicated in breast cancer progression. Expressed in stromal fibroblasts adjacent to epithelial tumour cells, the mechanism of MT1-MMP and MMP-11 induction remains unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
2
21
0
1
Order By: Relevance
“…In other fibrotic models, TGF-b stimulated MMP-2 and MMP-11 production (55)(56)(57)(58)(59)(60). Likewise, the TGF-b inhibitor perfenidone decreased MMP-11, but not MMP-2, in malignant glioma cells (61).…”
Section: Figurementioning
confidence: 95%
“…In other fibrotic models, TGF-b stimulated MMP-2 and MMP-11 production (55)(56)(57)(58)(59)(60). Likewise, the TGF-b inhibitor perfenidone decreased MMP-11, but not MMP-2, in malignant glioma cells (61).…”
Section: Figurementioning
confidence: 95%
“…Previous studies showed that the ECM regulates the activity of MT1-MMP (12,45). Therefore, we examined the impact of the ECM on ischemia-induced cleavage and/or loss of E-and N-cadherin.…”
Section: Effects Of Proteinase Inhibitors On Ischemia-induced Cadherimentioning
confidence: 99%
“…MMP11 in particular, a member of the matrix metalloproteinases, exhibits collagenolytic function against collagen VI under normal and malignant conditions (4), and is closely related to invasiveness and tumor progression (5). MMP-ll expression is simulated in mouse fibroblasts by cytokines, collagen and co-culture with human breast cancer cells (6), and its overexpression in lobular carcinoma cells of the breast promotes resistance to anoikis (7). MMP 11 is identified as the novel undetected gene of cervical carcinoma and contributes to the pathogenesis of cervical carcinoma (8).…”
mentioning
confidence: 99%